The Relationship Between Anemia and Quality of Life in Hemodialysis Patients at Moh Ridwan Meuraksa Level II Hospital - Dewi, Nurma; Sulistiya, Arie Apriani; Bedah, Sumiati (LPPM Universitas Mohammad Husni Thamrin, 2025)
Background: Chronic kidney disease (CKD) is a condition of permanent decline in kidney function, so that most patients require hemodialysis therapy. Hemodialysis can affect the physical, psychological, and social aspects of patients, which impacts the quality of life. One of the impacts / effects of chronic kidney failure undergoing hemodialysis is anemia. Untreated anemia can worsen physical conditions, reduce quality of life, and even increase the risk of premature death. Methods: The study used a quantitative cross-sectional approach. The sample was conducted using purposive sampling with calculations using the Slovin formula which obtained a total of 69 respondents. Anemia status was measured based on hemoglobin levels in the last 1 month, while quality of life was measured using the WHOQOL-BREF. Results: The results of the study showed that respondents who experienced anemia (Hb <10 mg/dL) were 69.6% and the majority of respondents had a poor quality of life of 58.0%. From the chi-square analysis, it was seen that there was a significant relationship between anemia and quality of life in chronic kidney failure patients, namely with a p-value of 0.027 (p <0.05). Discussion: A significant relationship between anemia and quality of life in hemodialysis patients is because anemia can cause symptoms such as fatigue, decreased physical activity ability, impaired concentration, and discomfort that affect the physical and psychological aspects of patients. This is in line with the theory that suboptimal oxygen supply due to low hemoglobin levels will disrupt organ function and overall quality of life. Conclusion: This shows a relationship between anemia and quality of life in hemodialysis patients at Moh Ridwan Meuraksa Class II Hospital.